Changes in the mitochondrial proteome of developing maize seed embryos - Wang, Wei‐Qing; Wang, Yue; Zhang, Qi; Møller, Ian M.; Song, Song‐Quan (Physiologia plantarum, 2018)
Mitochondria are required for seed development, but little information is available about their function and role during this process. We isolated the mitochondria from developing maize (Zea mays L. cv. Nongda 108) embryos and investigated the mitochondrial membrane integrity and respiration as well as the mitochondrial proteome using two proteomic methods, the two‐dimensional gel electrophoresis (2‐DE) and sequential windowed acquisition of all theoretical fragment ion mass spectra (SWATH). Mitochondrial membrane integrity and respiration were maintained at a high level up to 21 days after pollination (DAP) and decreased thereafter, while total mitochondrial number, cytochrome c oxidase activity and respiration per embryo exhibited a bell‐shaped change with peaks at 35–45 DAP. A total of 286 mitochondrial proteins changed in abundance during embryo development. During early stages of seed development (up to 21 DAP), proteins involved in energy production, basic metabolism, protein import and folding as well as removal of reactive oxygen species dominated, while during mid or late stages (35–70 DAP), some stress‐ and detoxification‐related proteins increased in abundance. Our study, for the first time, depicted a relatively comprehensive map of energy production by mitochondria during embryo development. The results revealed that mitochondria were very active during the early stages of maize embryo development, while at the late stages of development, the mitochondria became more quiescent, but well‐protected, presumably to ensure that the embryo passes through maturation, drying and long‐term storage. These results advance our understanding of seed development at the organelle level.